Konsep Kecerdasan Majemuk Howard Gardner - Syarifah Syarifah (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
The theory of Multiple Intelligences is revealed by Howard Gardner. In this theory, intelligence means the ability to solve problems or fashion products, that are valued in one or more cultural or community settings. This theory indicated that everyone has nine intelligences: linguistic, logical-mathematical, spatial, bodily-kinesthetic, musical, interpersonal, intrapersonal, naturalist, and existential. The multiple intelligences development can be done with educational methods included Islamic educational methods. This matter is done to establish the happy and humanist Islamic education process and to maximize child's multiple intelligences. ABSTRAK Teori Multiple Intelligences diungkapkan oleh Howard Gardner. Dalam teori ini, kecerdasan berarti kemampuan untuk menyelesaikan masalah atau produk fesyen, yang dinilai dalam satu atau lebih pengaturan budaya atau komunitas. Teori ini menunjukkan bahwa setiap orang memiliki sembilan kecerdasan: linguistik, logis-matematis, spasial, kinestetik-tubuh, musik, antarpribadi, intrapersonal, naturalis, dan eksistensial. Pengembangan kecerdasan ganda dapat dilakukan dengan metode pendidikan termasuk metode pendidikan Islam. Hal ini dilakukan untuk membangun proses pendidikan Islam yang humanis dan bahagia serta memaksimalkan kecerdasan ganda anak.